A multilayered genetic structure analysis between inflammatory bowel disease and bone density/osteoporosis - Mengting Qin; Xinhong Liu; Qinghua Luo; Ruyun Cai (PLoS ONE, 2025)
Background The association between inflammatory bowel disease (IBD) and reduced bone mineral density (BMD) or osteoporosis is still a subject of ongoing debate, underscoring the need for further exploration, particularly from a genetic perspective. Methods Utilizing data from genome-wide association studies on 59,957 IBD, 40,266 CD, 45,975 UC, 31,492 BMD, and 399,054 osteoporosis, comprehensive analyses were performed focusing on two main aspects: genetic correlations (Rg) and shared genetic loci. Initially, the overall Rg between these traits was assessed via genetic covariance analyzers and high-definition likelihood approaches. Following this, local genetic patterns were examined using local variant association analysis. Mendelian randomization (MR) analysis was performed to infer potential causal relationships. The genetic overlap was then explored using conditional/conjunctional false discovery rate (cond/conjFDR) statistical methods, leading to the identification of several biologically significant shared genetic loci. Results A notable genetic correlation was found between IBD, its subtypes, and BMD/osteoporosis at the genome-wide level. Additionally, significant local genetic associations were identified across various chromosomal regions. The conjFDR analysis further supported the genetic overlap and pinpointed several critical shared loci. Furthermore, significant enrichment of the Wnt signaling pathway was detected for both conditions. Conclusion This investigation offers robust genetic evidence supporting the comorbidity of IBD with BMD/osteoporosis, highlights possible underlying mechanisms, and provides new insights into clinical research and practice.